Relationship between Musculoskeletal Disorders and Ergonomic Working Conditions in Nurses - Jovilė Džervė; Anelė Katinė (Reabilitacijos Mokslai: Slauga, Kineziterapija, Ergoterapija)
Background. Nurses experience a higher prevalence of musculoskeletal disorders compared to other healthcare professions. Identifying unsafe work environments and mitigating ergonomic risk factors are crucial steps toward creating a safer workplace for nurses.